A loss of function mutation in CLDN25 causing Pelizaeus-Merzbacher-like leukodystrophy - Campbell, Matthew (My University, 2024)
Claudin-25 (CLDN-25), also known as Claudin containing domain 1, is an uncharacterized claudin family member. It has less conserved amino acid sequences when compared to other claudins. It also has a very broad tissue expression profile and there is currently a lack of functional information from murine knockout models. Here, we report a de novo missense heterozygous variant in CLDN25 (c.745G>C, p. A249P) found in a patient diagnosed with Pelizaeus-Merzbacher-like leukodystrophy and presenting with symptoms such as delayed motor development, several episodes of tonic absent seizures and generalized dystonia. The variant protein does not localize to the cell-cell borders where it would normally be expected to be expressed. Amino acid position 249 is located 4 amino acids from the C-terminal end of the protein where most claudin family members have a conserved binding motif for the key scaffolding protein ZO-1. However, CLDN-25 does not contain this motif. Here, we show that the C-terminal end of CLDN-25 is required for its junctional localization in a ZO-1 independent manner. The A249P mutant protein as well as a deletion mutant lacking its last 5 C-terminal amino cids also failed to localize to the cell-cell border in vitro. Intriguingly, cellular knockout of CLDN25, in vitro, appeared to increase the integrity of the tight junction between 2 contacting cells, while driving highly unusual increased movement of solutes between cells. We propose that the barrier function of CLDN-25 is akin to a decoy claudin, whereby decreasing its expression in “leaky” epithelial cells and endothelial cells will drive dynamic changes in the adhesion and interaction capacity of cell-cell contact points. While it remains unclear how this de novo CLDN-25 mutant induces leukodystrophy, our findings strongly suggest that this mutation induces haploinsufficiency of CLDN-25. Elucidating the function of this uncharacterized claudin protein will lead to a better understanding of the role of claudin proteins in health and disease.
PUBLISHED
Keywords: Claudin-25; Leukodysdrophy; tight junction; ZO-1